The effect of fluoxetine and imipramine on the improvement of depressive-like behaviors and HPA axis (hypothalamic-pituitary-adrenal cortex) activity – an animal model - Raghad Abdulsalam Khaleel (PC Technology Center, 2021)
Depression is one of the most common mental disorders and numerous medications are used to reduce the psychotic symptoms.